Analisis Determinan Kesempatan Kerja di Provinsi Sumatera Barat - Putri Andini; Idris (Media Riset Ekonomi Pembangunan (MedREP), 2025)
This study aims to analyze the determinants of employment opportunities in West Sumatra Province during the period 2017 to 2023. The approach used is quantitative, employing panel data regression methods and utilizing secondary data from the Central Bureau of Statistics (BPS). The variables analyzed include economic growth, education level, wages, and investment across 19 regencies/cities in West Sumatra Province. The estimation results show that simultaneously, economic growth, education level, wages, and investment collectively influence the increase in employment opportunities. Partially, economic growth has a positive and significant effect on increasing employment opportunities. Conversely, the education level shows a positive but not significant effect, while wages have a negative effect, and investment has a positive but not significant effect on employment opportunities. These findings indicate that economic growth plays a crucial role in generating employment opportunities, whereas the other variables have not yet demonstrated a strong contribution. Therefore, active government involvement is required to enhance employment opportunities, including through labor-intensive sectors that can absorb a large workforce.